2008
DOI: 10.1017/s1092852900017120
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Prediction of Treatment Response in Depression:Integration of Clinical, Cognitive, Psychophysiological, Neuroimaging, and Genetic Measures

Abstract: Antidepressants are important in the treatment of depression, and selective serotonin reuptake inhibitors are first-line pharmacologic options. However, only 50% to 70% of patients respond to first treatment and <40% remit. Since depression is associated with substantial morbidity, mortality, and family burden, it is unfortunate and demanding on health resources that patients must remain on their prescribed medications for at least 4 weeks without knowing whether the particular antidepressant will be effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 241 publications
3
105
1
3
Order By: Relevance
“…These include the international study to predict optimized treatment in depression (iSPOT-D). 2 Further, to explore temporal dynamics and reciprocal relations, longitudinal or experimental data need to be applied; for instance to confirm the direction of effects between body arousal and the neuroticism measure of emotional stability. It would also be interesting to examine if there are additional interactions between BDNF alleles and sex differences, given previous indications of such differences in relation to temperament.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the international study to predict optimized treatment in depression (iSPOT-D). 2 Further, to explore temporal dynamics and reciprocal relations, longitudinal or experimental data need to be applied; for instance to confirm the direction of effects between body arousal and the neuroticism measure of emotional stability. It would also be interesting to examine if there are additional interactions between BDNF alleles and sex differences, given previous indications of such differences in relation to temperament.…”
Section: Discussionmentioning
confidence: 99%
“…52 Met allele carriers show comparatively lower hippocampal gray matter 53,54 and poorer cognitive performance. 2,3,52,54 It has also been shown that, in otherwise healthy individuals with the BDNF Met variant, low emotional stability (higher neuroticism) with higher syndromal depression is associated with lower hippocampal volume. 55 Animal evidence indicates that stress exacerbates the effects of reduced BDNF on both hippocampal networks and autonomic arousal.…”
Section: -51mentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, robust algorithms predicting treatment response will need to incorporate genetic testing (Frieling andTadic, 2013), pharmacogenetics (de Leon, 2009), and neuroendocrine function (Holsboer, 2000). It is also well documented that a number of patient factors predict response to antidepressant treatment across treatment modalities, including disease severity, longer duration and frequency of the episodes, comorbid anxiety disorders, and an older age of onset (Kemp et al, 2008). Moreover, longitudinal clinical followup data would be critical to assess relapse after BATD termination as well as rs-fcMRI predictors of relapse, and posttreatment resting-state scans would be needed to address potential mechanisms of antidepressant action on canonical resting-state brain networks.…”
Section: Discussionmentioning
confidence: 99%
“…Most published prediction studies report predictors associated with better or poorer response to a single treatment [4].…”
mentioning
confidence: 99%